Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12938-016-0248-0
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics study of a multilayer stent for the treatment of aneurysms

Abstract: BackgroundThe changes of hemodynamics caused by the implantation of multilayer stent (MS) have significant effects for aneurysm sac.MethodsComparisons of 3D numerical models with/without a MS in an abdominal aortic aneurysm with a 90° branch vessel were numerically studied from the viewpoint of hemodynamics.ResultsThe results showed that: (1) The flow fields and Wall Shear Stress (WSS) are changed dramatically after MS implantation. The velocity of the blood flow in aneurysm sac decreases significantly and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Recently, interest in MS has increased significantly as a result of its success in clinical application. However, as previous numerical simulations found that two-layer stents had little impact on the pressure on the aneurysm wall 16 , combinations of SG and MS were presented to obtain better isolation, but the coverage of SG still confuses doctors during the intraoperative period.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, interest in MS has increased significantly as a result of its success in clinical application. However, as previous numerical simulations found that two-layer stents had little impact on the pressure on the aneurysm wall 16 , combinations of SG and MS were presented to obtain better isolation, but the coverage of SG still confuses doctors during the intraoperative period.…”
Section: Discussionmentioning
confidence: 95%
“…These are 3-layer stents designed to laminate the flow through the aneurysm so that it gradually becomes thrombotic without affecting the flow in the branches, simultaneously decreasing the peak stress on the aneurysm wall. 4 This feature is particularly important in the aortic arch and thoracoabdominal region.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of CFD and MRI/CT images, the formation of atherosclerotic lesions can be accurately predicted, and haemodynamic parameters can be assessed [19]. Feasibility of incorporating data obtained from CT/MRI in numerical studies is demonstrated in [20]. A potential risk factor of artery geometry resulting in exaggerated atherosclerosis was investigated [21].…”
Section: Introductionmentioning
confidence: 99%